2020
DOI: 10.3390/nu13010115
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality Is Associated with Serum Antioxidant Capacity in Women with Breast Cancer: A Cross Sectional Study

Abstract: Oxidative stress produced by adjuvant treatments is associated with cell injury; however, a healthy diet can help mitigate it. The aim of this study is to investigate the association between diet quality and oxidative stress parameters in women subjected to adjuvant treatment for breast cancer. The sample comprised 70 women. Oxidative stress biomarkers and diet quality parameters based on the Brazilian Healthy Eating Index—Revised (BHEI-R)—were evaluated at baseline (p0) and after adjuvant treatment (p1). Ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Additionally, Yeon et al [65] found an inverse association between vitamin A and β-carotene intake and 8-OH-dG levels in women with breast cancer. Contributing to the present results, we showed in a recent publication that diet quality score, which includes eating fruits and vegetables according to the Brazilian recommendation for a healthy diet, is positively associated with serum FRAP levels in women diagnosed with breast cancer [55].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Additionally, Yeon et al [65] found an inverse association between vitamin A and β-carotene intake and 8-OH-dG levels in women with breast cancer. Contributing to the present results, we showed in a recent publication that diet quality score, which includes eating fruits and vegetables according to the Brazilian recommendation for a healthy diet, is positively associated with serum FRAP levels in women diagnosed with breast cancer [55].…”
Section: Discussionsupporting
confidence: 79%
“…It appears that these results indicate that women showing highest DaC before beginning adjuvant treatment and during it exhibit some kind of protection against the aggravation of oxidative stress. This is an expected consequence in women submitted to adjuvant treatment for breast cancer [55,56], since the aim of it is killing breast cancer cells by exacerbating oxidative stress [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study from the same original sample, we have shown that a higher diet quality score was associated with higher ferric antioxidant power (FRAP), a biomarker of antioxidant defense in serum, before adjuvant treatment for breast cancer began [ 11 ]. Herein, the protective effect of diet quality before the beginning of adjuvant chemotherapy on the chance of developing food aversion may be linked to increased serum antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one of the main causes of food aversions in response to adjuvant chemotherapy is increased oxidative stress [ 10 ]. We have already demonstrated that diet quality and a diet rich in antioxidants can help mitigate the excess production of reactive oxygen species [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a large number of clinical practices have shown that these treatment methods encounter the problems of primary and secondary drug resistance, which has become a major treatment obstacle that is difficult to avoid in clinical practice [ 1 , 2 ]. For example, luminal A and luminal B breast cancers account for 70% to 80% of all types of breast cancer, respectively; approximately 70% of patients had effective initial drug treatment; and approximately 30% of patients had resistance to primary endocrine therapy [ 3 ]. Nearly 50% of HER2-amplified breast cancers are resistant to herceptin at the beginning, and secondary resistance appears approximately one year after treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%